ANALYSIS OF EMPLOYEE ENGAGEMENT AND COMPANY PERFORMANCE - Silalahi, Immanuel Maradopan; Saerang, David P.E.; Mekel, Peggy A. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Employee could be a competitive advantage of a company if company manages its employees well. The success of a company could be seen from how a company manages their employees and engages their employees. Most of big companies put their employees in top priority in order to keep their top performance. These big companies manage their employees and try to engage their employees so that their employees could generate high performance. In this study, employee engagement is the factor to examine the company performance. The aim is to examine the influence of employee engagement to employee performance and company performance. Theories that are supporting this research are human resource management and theories of employee engagement from other researchers. This research is a literature review research using qualitative method. From several of researches about employee engagement, this research finds that employee engagement has positive relationship with company performance. The environment of the company, such as the physical space and climate of the environment support the employee engagement process. The person itself, such as the personality, the physical traits, the emotion of the person, also support the process of employee engagement. Keywords: employee engagement, company performance